[BOOK REVIEW] Refugees, Regionalism, and Responsibility - Jenica Alva (Faculty of Law, Universitas Padjadjaran, 2019)
Penelope Mathew is a Professor of International Law and a Dean in Griffith Law School, Australia. She is a profound researcher in refugee law topics. She is admired for her innovative idea to promote regionalism as a tool for governments to leverage better protection for refugees. Studying an underexplored topic, Mathew is able to synthesize the complexity of regionalism in a simple manner to be understood easily by readers. The book is divided into two parts. The first part consists of three sub-parts: (1) regionalism position in international politics and refugee law; (2) philosophical and ethical reasons of states’ responsibility in the case of refugees; and (3) steps and actions for states to share responsibility in handling refugees. The second part looks at the regional arrangements for the protection of refugees in some detail, whether they have resulted in better refugee protection and durable solutions. DOI: https://doi.org/10.22304/pjih.v6n3.a11